The Mediation Role of Strategic Orientation between Human Resource Management and Organizational Performance: Evidence from Maldivian Hotels and Resorts - Hawwa, Nazla Zubair (2013)
Prior research evidence has been set on the relationship between human resource management and performance relationship. Yet, very little has been comprehended on exactly the vehicle that drives this relationship of human resource to organizational performance. In response to the call to explore this hidden element of the mechanism through human resource strategies work to achieve a higher performance, this study is designed to extend the previous work by examining the relationship between human resource strategies and strategic orientation and organizational performance in terms of financial and non-financial performance. Specifically, this research probes into the relationship between human resource strategies developed by Dyer and Holder (1998) (involvement, investment and inducement strategies) and strategic orientation developed by Miles and Snow (1978) (prospector, defender, analyzer and reactor strategic orientation), and organizational performance in relation to financial and non-financial performer of 101 hotels and resorts based in the Maldives. The questionnaires were distributed to the hotels and resorts using convenient sampling. The research hypotheses were tested using PLS estimation technique version 2.0 while descriptive analysis was done using SPSS statistical software version 20. This research revealed the significant effect human resource strategies have on strategic orientation and also the positive influence of strategic orientation to both financial and non-financial performance. This study also established the mediation role of strategic orientation in driving the human resource strategies to non-financial performance. However, no such mediation was found in the relationship between human resource strategies to financial organizational performance. The discussion collates the empirical evidence and contribution. Theoretical and practical implications as well as recommendations for future research are provided.